Analisis Sumber Dan Tingkatan Konflik Dalam Organisasi: Kajian Literature Review Sistematis Pada Konteks Pendidikan Dan Manajemen Organisasi - Ika Septi Wulandari; Mu’alimin, Mu’alimin (CV. ITTC INDONESIA, 2026)
Conflict is a phenomenon that cannot be separated from organizational life, including in educational institutions. Differences in individual backgrounds, interests, leadership styles, and communication patterns often become factors that trigger the emergence of conflict within organizations. Therefore, understanding the sources of conflict and the levels of conflict is important to create a conducive organizational environment that supports the performance of organizational members. This study aims to examine and analyze previous studies related to the sources and levels of conflict in educational organizations using a literature review approach. The research method used is a systematic literature review by examining scientific articles relevant to the research topic. The search for articles was conducted through the Google Scholar database and the Publish or Perish (PoP) application by entering keywords related to the research topic. The criteria for the selected articles include scientific articles published in journals and conference proceedings within the last five years (2020–2025) and openly accessible to the public. Based on the initial search results, 50 articles were obtained. After the screening and selection process based on topic relevance, 5 scientific articles were selected for further analysis. The results of the review indicate that the sources of conflict in educational organizations generally originate from differences in interests, cultural backgrounds, leadership styles, ineffective communication, and work motivation. Conflicts can occur at various levels, namely intrapersonal conflict, interpersonal conflict, group conflict, and organizational conflict. Furthermore, psychological management and organizational leadership approaches play an important role in managing conflicts so that they do not hinder organizational performance and can even be utilized as a means to improve performance and the quality of working relationships within educational organizations.